Joint Optimization of Trajectory and Handover Strategy for Cellular-Enabled UAV - Hyeon-Seong Im; Kyu-Yeong Kim; Jaehoon Chung; Si-Hyeon Lee (IEEE Access)
We consider a scenario where a UAV travels from an initial point to a final point while maintaining connectivity with the cellular network. For this scenario, the problem of jointly optimizing UAV trajectory and handover strategy to travel between the two points swiftly while avoiding overly frequent handovers is formulated. For this optimization problem, we propose an algorithm that involves converting the original problem into the problem of finding the minimum weight path over a weighted finite graph which can be solved in polynomial time. Our proposed algorithm is compared with some existing algorithms in terms of performance and time complexity, and it is shown that our algorithm is the only one that outputs an optimal solution in polynomial time. Furthermore, various numerical results are presented to illustrate optimal UAV trajectories and handover strategies according to environments.